On Marriage Dynamics and Fertility in Malawi: How Does Remarriage Affect Fertility Preferences and Childbearing Behaviour? - John, Benson (Centre for Actuarial Research (CARE), 2018)
The interplay between remarriage and fertility is among the most poorly documented subjects in sub-Saharan Africa, yet remarriage is one of the fundamental aspects of marriage dynamics in the region. Referring to classical demographic and statistical techniques, this research uses data collected since 1992 from Malawi Demographic and Health Surveys to establish the pattern and level of union dissolution and remarriage, and to assess the influence of remarriage on fertility preference and childbearing. The results reveal increasing stability of unions over time and a declining proportion of remarried women. The probability of experiencing first union dissolution within 15 years dropped from 45.9 to 40.0 per cent between 1992 and 2015, while the comparable likelihood of remarriage decreased from 36.1 to 27.7 per cent over the same interval duration. The effect of remarriage on the desire for more children is positive at advanced interval durations relative to the onset of first marriage. At shorter interval periods, where remarriage is relatively most recent, remarriage inhibits the desire for additional children. For example, in 2015, among women who first married 15-19 years before the survey, the odds of desiring another child were 4 per cent significantly higher among remarried women relative to their counterparts in intact unions. In contrast, for women who were married for 0-5 years, remarried women had 3 per cent lower olds of desiring another child. Furthermore, the childbearing pattern of remarried women is found to be distinct from that of women in intact unions. Remarried women give birth to more children sooner than their counterparts in intact unions, but eventually end up with fewer children. Indeed, the results show that in 2015, women in intact unions had 0.4 more children on average than their remarried counterparts. However, the difference in complete family size is steadily diminishing (difference of 1.5 in 2000), largely due to more marked fertility decline among women in intact unions. This trend, together with the long-term pattern of cumulated fertility differentials at younger reproductive ages, and current fertility disparities over the past two decades, strongly reveals that a new regime, where remarried women will end up with higher complete family size than those in intact unions, is emerging.